Experimental and Numerical Investigation on the Ultimate Bearing Capacity of Axially Compressed Steel Tube Columns with Local Corrosion - Wei Fang; Tao Wang; Mengcheng Chen; Mingyang Zhang; Hong Huang; Kaicheng Xu; Qingqing Wen (Buildings)
In this paper, 17 types of circular, hollow steel tube columns were designed for the axial compression test. A defect was corroded with an acid rain spray method. The effects of the geometric spatial location of local corrosion zones, three-dimensional size, shape, and number of local corrosion zones on the axial compression load-bearing capacity of the circular hollow steel columns were investigated. Through model verification and parameter analysis in the finite element software ABAQUS, a finite element model of 136 local corrosion, hollow steel tube columns under axial compression was established. In conjunction with experimental and numerical analysis, the primary factor influencing the load-bearing capacity of the steel tube columns was the decrease in effective cross-sectional zones at the corroded zones. Single or multiple local corrosion zones of the same size distributed along the length of the column can reduce the load-bearing capacity of steel tube columns. However, the number, location, and distribution of corrosion zones with the same size have similar degrees of influence on the load-bearing capacity of the steel tube column, with no significant differences. In the case of the same corrosion ratio η, the load-bearing capacity of steel tube column exhibits a linear relationship with the increase in both the radial corrosion thickness and the circumferential corrosion width within the locally corroded zone. The axial corrosion length in the corroded region has little effect on the load-bearing capacity of the steel tube columns. Ranking the effect of corrosion parameters on the axial compression bearing capacity under the same corrosion ratio η, the largest one is the radial corrosion thickness; the next are the circumferential corrosion width and the axial corrosion length. A practical formula was developed to calculate the load-bearing capacity of locally corroded steel tube columns, using the rate of section loss in the corroded region as the dependent variable. The formula accurately calculates the axial compressive load-bearing capacity of locally corroded steel tube columns and provides valuable reference for evaluating and maintaining steel tube structures.